2016
DOI: 10.1086/687228
|View full text |Cite
|
Sign up to set email alerts
|

Validating a Noninvasive Technique for Monitoring Embryo Movement In Ovo

Abstract: Avian embryos are a commonly used model system for developmental studies, but monitoring of physiological parameters such as heart rate (HR) and movement in ovo poses a challenge to researchers. These are also increasingly common research objectives for ecological and embryo behavior studies in oviparous species. We therefore explored the validity of a new digital egg-monitoring system for the noninvasive monitoring of these parameters. We tested the relationship between frequency-ofmovement values gathered by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
0
13
0
4
Order By: Relevance
“…Also, the disturbed balance of contributions by channels to electrical activity or the malfunction of even one of them (Kodirov et al, ) might result in abnormalities in rhythm, for example, ectopic beat resulting from an early after depolarization (EAD; Figure ). In fertilized eggs, the exposure of E15 chick to ~21 mM 4‐AP facilitated the HR and motility but this “we suggest is due to observer error in distinguishing individual movements when embryos are moving multiple body parts or moving very frequently” (Pollard, Pitsillides, & Portugal, ). Because the eggs of lizards, that is, brown anole Anolis sagrei , is relatively small, it takes only ~3 min on average to reach the temperature of the environment 22 versus 32°C of incubator (Hulbert et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the disturbed balance of contributions by channels to electrical activity or the malfunction of even one of them (Kodirov et al, ) might result in abnormalities in rhythm, for example, ectopic beat resulting from an early after depolarization (EAD; Figure ). In fertilized eggs, the exposure of E15 chick to ~21 mM 4‐AP facilitated the HR and motility but this “we suggest is due to observer error in distinguishing individual movements when embryos are moving multiple body parts or moving very frequently” (Pollard, Pitsillides, & Portugal, ). Because the eggs of lizards, that is, brown anole Anolis sagrei , is relatively small, it takes only ~3 min on average to reach the temperature of the environment 22 versus 32°C of incubator (Hulbert et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, essas são invasivas e robustas, exigindo equipamentos que impedem sua utilização a campo ou na prática comercial, além de possuírem elevado risco de introdução de infecção. Tais práticas dificultam o acompanhamento do desenvolvimento embrionário em sistemas de criação, bem como para a maioria dos estudos e projetos que envolvam espécies ameaçadas (Pollard et al, 2016).…”
unclassified
“…O monitor digital Egg Buddy ® (Avian Biotech) detecta movimentação por meio de luz infravermelha, a qual ultrapassa a casca do ovo, captando pulsação de sangue nos vasos ou movimentos embrionários. Esse dispositivo já foi usado com sucesso para monitorar a saúde de embriões em trabalhos de conservação de espécies (Angilletta et al, 2013), assim como em pesquisas envolvendo fisiologia de ovos e desenvolvimento de embriões (Lima et al, 2011;Pollard et al, 2016;Pollard et al, 2017).…”
unclassified
“…In human foetuses, heart rate increases linearly with foetal movement (DiPietro et al, 2001). In chicken embryos, on the other hand, Pollard et al (2016) found that higher heart rate correlated with fewer embryonic movements. However, these findings may have been a result of overheating.…”
Section: Embryonic Activitymentioning
confidence: 96%
“…However, these findings may have been a result of overheating. Pollard et al (2016) incubated their eggs at a constant air temperature of 37.0°C. Air temperature can differ greatly from temperature at the embryo's level, because of differences in embryonic heat production or heat transfer from the egg .…”
Section: Embryonic Activitymentioning
confidence: 99%